Simultaneous delivery of olaparib and carboplatin in PEGylated liposomes imparts this drug combination hypersensitivity and selectivity for breast tumor cells - Novohradsky, Vojtech; Zajac, Juraj; Vrana, Oldrich; Kasparkova, Jana; Brabec, Viktor (Oncotarget, 2018)
Combination regiments involving platinum anticancer drugs and agents with unrelated mechanisms of action are a subject of widespread interest. Here, we show that synergistic toxic action in cancer cells of combinations of antitumor platinum drug carboplatin and effective PARP inhibitor olaparib is considerably improved if these combined drugs are encapsulated into liposomes. Notably, the formation of such nano-formulations, called OLICARB, leads to a marked enhancement of activity in human cancer cell lines (including those resistant to conventional platinum antitumor drugs) and selectivity towards tumor cells. We used immunofluorescence analysis of γH2AX expression and examined DNA damage in cancerous cells treated with the investigated compounds. We find that the synergistic toxic effects in cancer cells of both drugs used in combination, nonencapsulated or embedded in the OLICARB nanoparticles, positively correlates with DNA damage. These results also suggest that the enhancement of the toxic effects of carboplatin by olaparib in cancer cells is a consequence of an accumulation of cytotoxic lesions in DNA due to the inhibition of repair of platinated DNA augmented by the synergistic action of olaparib as an effective PARP inhibitor. Our findings also reveal that the combination of olaparib with carboplatin encapsulated in the OLICARB nanoparticles is particularly effective to inhibit the growth of 3D mammospheres. Collectively, the data provide convincing evidence that the encapsulation of carboplatin and olaparib into liposomal constructs to form the OLICARB nanoparticles may represent the viable approach for the treatment of tumors with the aim to eliminate the possible effects of acquired resistance.
Keywords: antitumor activity; liposomes; carboplatin; olaparib; combination